ANALISIS PENGUJIAN TAHANAN ISOLASI TRANSFORMATOR ARUS 70KV BAY KUNINGAN II DI GARDU INDUK SUNYARAGI CIREBON - Lety Hatiffatul Nur; Ulinnuha Latifa (Power Elektronik : Jurnal Orang Elektro, 2022)
Abstract - At the substation there are equipment that is intended as a transmission regulator, one of which is a current transformer. "Current transformer (CT) is a device used to convert a high current value into a lower current value for measurement and protection purposes, and also to isolate the secondary circuit from the primary circuit." The research was conducted by comparing the results of the current transformer insulation resistance test with the VDE Catalouge 228/4 insulation resistance. Based on the results of the insulation resistance test at each core of the current transformer, each phase has a value of 1GΩ. Analysis of the average value obtained on the current transformer produces 14.28 MΩ, so the conclusion obtained is that the Bay Kuningan II 70KV at Sunyaragi substation UPT CIREBON current transformer (CT) is in good condition based on the VDE Catalouge 228/4 insulation resistance standard. Keywords – Current Transformator (CT), CT test, Insulation Resistance Abstrak - Pada gardu induk terdapat peralatan peralatan yang diperuntukkan sebagai pengatur transmisi, salah satunya, adalah transformator arus /CT. “Transformator arus (CT) adalah perlengkapan alat yang dipakai untuk mengonversikan besaran nilai arus yang tinggi menjadi nilai arus yang lebih rendah untuk kebutuhan pengukuran dan proteksi, dan juga untuk mengisolasi rangkaian sekunder terhadap rangkaian primer.”. Penelitian yang dilakukan adalah dengan membandingkan hasil pengujian tahanan isolasi transformer arus dengan tahanan isolasi VDE Catalouge 228/4. Berdasarkan hasil pengujian tahanan isolasi pada setiap inti transformer arus masing-masing fasa memiliki nilai sebesar 1GΩ. Analisa nilai rata- rata yang diperoleh pada  transformer arus menghasilkan 14,28 MΩ, sehingga kesimpulan yang didapatkan adalah Transformator arus (CT) Bay Kuningan II 70KV di Gardu Induk Sunyaragi UPT CIREBON dalam keadaan baik berdasarkan  standar tahanan isolasi VDE Catalouge 228/4.